Adherence to a Mediterranean-like Diet as a Protective Factor Against COPD: A Nested Case-Control Study. (4th July 2019) - Fischer, Alexandra; Johansson, Ingegerd; Blomberg, Anders; Sundström, Björn
Abstract: A diet rich in nutrients has been suggested to have protective effects against the development of chronic obstructive pulmonary disease (COPD). Since the traditional Mediterranean diet is high in nutrients, including antioxidants, vitamins, and minerals, it is of interest to study as a protective factor against COPD. Our aim was therefore to study its associations with development of COPD using population-based prospective data from the Västerbotten Intervention Programme (VIP) cohort. Data on diet from 370 individuals, who later visited the Department of Medicine at the University Hospital, Umeå, Sweden, with a diagnosis of COPD, were compared to 1432 controls. Adherence to a Mediterranean diet was assessed by a modified version of the Mediterranean diet score (MDS). Cases were diagnosed with COPD 11.1 years (mean) (standard deviation [SD] 4.5 years) after first stating their dietary habits in the VIP at a mean age of 55.5 years (SD 6.6 years). Higher MDS was associated with a higher level of education and not living alone. After adjustment for co-habiting and education level, individuals with an intermediate MDS and those with the highest MDS had a lower odds of developing COPD (odds ratio [OR] 0.73, 95% confidence interval [CI] 0.56–0.95; OR 0.56, 95% CI 0.37–0.86, respectively). These results remained also after adjustment for smoking intensity, i.e., numbers of cigarettes smoked per day (OR 0.73, 95% CI 0.53–0.99; OR 0.59, 95% CI 0.35–0.97), respectively). To conclude, adherence to a Mediterranean-like diet seems to be inversely associated with the development of COPD.